Pendidikan Anak dalam Lingkup Keluarga Menurut Al-Qur’an - Ade Salamun; Didin Hafidhuddin; Akhmad Alim (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The modern era has an impact on the decline in the function of the family in children's education, even though the family has a very important function in the formation of children's character. The hadith of the Prophet SAW also said,